TIPOLOGI MADRASAH IBTIDAIYAH BERBASIS PESANTREN PERSPEKTIF PERUBAHAN SOSIAL TALCOTT PARSONS - Aji Pangestu; Isa Anshori (Sekolah Tinggi Agama Islam Muhammadiyah Blora, 2024)
This study aims to describe the typology of Islamic boarding school-based madrasah and analyze the transformation process using the theory of social change with Talcott Parsons' AGIL scheme. This qualitative descriptive-analytic study was conducted at MI Al Fitrah Surabaya. Interviews, observation, and documentation were use to collect data. The results of this study revealed that; (1) The establishment of MI Al Fitrah is a form of adaptation to the response to social change in society. (2) MI Al Fitrah sets out the goals to be achieved as the fulfillment of changes that occur in society through the vision of